Algunos aspectos de la política fiscal en el Ecuador - Ruales, Wilson (1997)
This article was scanned by the Biblioteca Ecuatoriana Aurelio Espinoza Pólit. For several decades, the fiscal situation has been one of the main problems facing the Ecuadorian economy and has determined a good part of the adjustments aimed at overcoming the prevailing distortions in the economy. This paper will address some of the most important aspects related to fiscal policy without, as is to be expected, attempting to exhaust the subject given its breadth and complexity, which far exceeds the limited space that has been established for this paper, as well as the short time available to discuss it.